2020
DOI: 10.1177/0022034520917368
|View full text |Cite
|
Sign up to set email alerts
|

Silver Diamine Fluoride in Children Using Physiologically Based PK Modeling

Abstract: Silver diamine fluoride (SDF) is used topically to prevent or arrest dental caries and has been tested clinically in toddlers to elderly adults. Following SDF application, small quantities of silver can be swallowed and absorbed. To monitor silver concentrations, pharmacokinetic studies can be performed. However, pharmacokinetic studies are time-consuming, resource intensive, and challenging to perform in young children. The objective of this study was to develop a physiologically based pharmacokineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In a study on adults, Vasquez et al ( 2012 ) described the pharmacokinetics of SDF after oral application, concluding that serum concentrations of fluoride and silver demonstrated a low risk of toxicity when used only occasionally in this population. In a study on rats, Chen et al ( 2020 ) suggested that the conventional application of SDF on the teeth to prevent or stop dental caries results in silver concentrations in plasma and tissue that were far below toxic levels.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on adults, Vasquez et al ( 2012 ) described the pharmacokinetics of SDF after oral application, concluding that serum concentrations of fluoride and silver demonstrated a low risk of toxicity when used only occasionally in this population. In a study on rats, Chen et al ( 2020 ) suggested that the conventional application of SDF on the teeth to prevent or stop dental caries results in silver concentrations in plasma and tissue that were far below toxic levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies, however. have explored the possible toxic effects of silver(I) ion exposure from SDF [ 38 ]. The silver content of small amounts of SDF used to treat tooth decay results in a very low exposure, and therefore systemic silver toxicity should not represent a major concern to clinicians.…”
Section: Toxicities Of Fluorides and Their Excessive Usementioning
confidence: 99%
“…One aticle addressed potential toxicity of SDF based on a pharmacokinetic model to predict silver disposition in children. 300 The mathematical model was assessed by comparing the predicted values of physiologic silver concentrations with data from published animal and human studies after the oral ingestion of silver. The mathematically predicted silver concentrations were within the 95% confidence interval of observed plasma and tissue concentrations in the animal and human data.…”
Section: Dental Materials and Therapeuticsmentioning
confidence: 99%